On Anacroneuriini (Plecoptera: Perlidae) morphology: Standardizing vocabulary and a morphological atlas - Gastaldo, Rodrigo Braga; Almeida, Lucas Henrique de [UNESP]; Salles, Frederico Falcão (Elsevier, 2025)
Anacroneuriini is a tribe of stoneflies within Perlidae which displays diagnostic characteristics in their male genitalia. As researchers are often focused on a few taxonomic characters of each particular genus, they rarely consider the morphological terminology of the tribe as a whole. As such, over time many different names for the same morphological structures have been coined, making it difficult to describe new species and semaphoronts accurately in a standardized way. Systematics may also struggle in determining primary homologies from the lack of comparable vocabulary between species and genera. The objective of this work is to provide a morphological atlas of Anacroneuriini, disclosing standardized names of each external morphological trait of the four different genera of the tribe. Specimens from Museu de Entomologia, Universidade Federal de Viçosa (UFVB) were analyzed, photographed and illustrated. Terminology primarily followed morphological accuracy based on homologies, while name recurrence in recent literature was used as secondary criteria. The resulting atlas is the first to gather detailed information on all body regions of all genera of Anacroneuriini. The atlas is useful as a resource both for beginners in Anacroneuriini research and experienced researchers alike, providing standard terminology with clear illustrations for species description, identification and general taxonomic work.
Keywords: Anacroneuria; Enderleina; External morphology; Kempnyia; Macrogynoplax; Stoneflies